Migration of Afro-Asian Monsoon Fringe Since Last Glacial Maximum - Cheng, Jun; Ma, Yiyi; Wu, Haibin; Long, Hao; Liu, Zhengyu (Frontiers in Earth Science, 2020)
Geological records indicated the termination of the Holocene Thermal Maximum (dramatic drying) occurred progressively later at lower latitudes in both North Africa and East Asia, along with the coherent weakening of local summer monsoon. Here we show that this time-transgressive evolution was dominated by the southward migration of monsoon fringe (shrinking monsoon domain) under monsoon weakening, as illustrated in a transient climate-terrestrial ecosystem model simulation. The monsoon fringe retreating southward during the Holocene, as well as expanding northward during the last deglaciation, occurred synchronously in a belt extending from North Africa to East Asia, which induced a locally humid-arid transition and the subsequent dramatic environment impact. The migration of Afro-Asia monsoon fringe since the Last Glacial Maximum was modulated by the orbital forcing through its impact on land-ocean thermal contrast, aiding by the variation of CO2 concentration.